Psychosis Screening Practices in Schools: A Survey of School-Based Mental Health Providers - Kline, Emily (Early Interv Psychiatry, 2018)
AIM: Many school districts in the United States employ mental health professionals to provide assessment, counseling and crisis interventions within the school setting; however, little is known about actual clinical practices of psychosis screening in schools. The aim of the present study is to examine attitudes and practices regarding psychosis screening among school mental health providers in metropolitan Boston, Massachusetts. METHODS: School-based mental health clinicians (N = 100) completed an anonymous survey assessing familiarity, screening, and involvement with psychosis and psychosis risk prior to attending trainings on psychosis. RESULTS: Providers reported screening for psychosis less often than other mental health problems and rated themselves as less confident treating psychosis relative to other mental health concerns. Frequency of screening for psychosis was significantly associated with familiarity with psychosis assessment and case management, confidence providing treatment for individuals experiencing psychosis, and the number of students with or at risk for psychosis with whom providers had been involved. Frequency of screening for psychosis was not associated with years of practice, suggesting that both novice and experienced school-based providers may benefit from training on this issue. CONCLUSIONS: Community outreach via school-based provider training on assessment and management of psychosis may help to increase providers’ understanding of psychosis and increase the practice of verbal or written screening for psychosis and psychosis risk within schools.